Response of alfalfa growth and rhizosphere properties to soil phosphorus supply and mowing in a salt-affected soil - Tian, Junjie; Wan, Weifan; Liu, Qian; Zhao, Bayinnamula; Li, Haigang (Frontiers in Plant Science, 2025)
IntroductionPhosphorus (P) deficiency is a key limiting factor for alfalfa quality and yield in salt- affected soils, and root exudates are considered as a strategy for alfalfa P acquisition under P stress, which requires the supply of photosynthetic products.However, mowing may reduce the supply of photosynthetic products by decreasing photosynthetic rate and chlorophyll yield, which can affect the concentration of alfalfa root exudates in saline soil. This study aimed to investigate the possible mechanism of increasing P utilization rate with different P application rates after mowing. MethodsField and pot experiments were conducted with alfalfa grown under five P application rates (0, 60, 120, 180 and 240 kg ha-1). Plant growth, shoot P concentration, rhizosphere carboxylates concentration, rhizosphere acid phosphatase (APase) activity and rhizosphere pH were measured. Results and discussionP application significantly improved plant height and branch number, with the highest levels observed when P application rate was 180 kg ha-1. Crude protein content was also improved (13.3%-23.3%) with increasing P application rates and reached the maximum when P application rate was 240 kg ha-1. The yield of alfalfa increased with higher shoot P concentration. Furthermore, mowing significantly reduced rhizosphere carboxylates concentration (30.4%-100%) and APase activity (39.8%-75.0%) across all P treatments. However, these reductions were less pronounced when the P application rate exceeded 120 kg ha-1. In contrast, rhizosphere pH was unaffected by mowing across different application rates. Overall, this study demonstrates that P fertilization not only promotes alfalfa growth and quality in salt-affected soil but also mitigates the adverse effects of mowing on rhizosphere carboxylates concentration and APase activity. This highlights the potential of P fertilization to reduce P fixation and enhance P uptake by regulating rhizosphere-activated soil P dynamics after mowing. These findings provide a basis for enhancing the P utilization rate after mowing. The research results provide a basis for improving P utilization after mowing, enabling farmers to formulate scientific mowing strategies in production, thereby enhancing the yield and quality of alfalfa.